1999
DOI: 10.1002/(sici)1097-4628(19990801)73:5<777::aid-app18>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion polymerization of tetrafluoroethylene: effects of reaction conditions on the polymerization rate and polymer molecular weight

Abstract: The emulsion polymerization of tetrafluoroethylene (TFE) was carried out in a semibatch reactor using a chemical initiator (ammonium persulfate) and a fluorinated surfactant . The effects of the reaction condition were investigated though the polymerization rate, molecular weight of polytetrafluoroethylene (PTFE), and stability of the dispersion. The emulsion polymerization of TFE was different from conventional emulsion polymerization. The polymerization rate was suppressed when the polymer particles were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Other configurations reported include unbaffled reactors with anchor-type agitators 97 and horizontal reactors with paddle-type agitators (these are mostly used in copolymerization). Kim et al 53 investigated the efficacy of various stirrer types for TFE polymerization and found that vortex formation and the maximization of gas-to-liquid surface area are the most important criteria to look at when selecting a stirrer. They recommend the use of an anchor-type stirrer with a baffled tank.…”
Section: Polymerization Equipmentmentioning
confidence: 99%
“…Other configurations reported include unbaffled reactors with anchor-type agitators 97 and horizontal reactors with paddle-type agitators (these are mostly used in copolymerization). Kim et al 53 investigated the efficacy of various stirrer types for TFE polymerization and found that vortex formation and the maximization of gas-to-liquid surface area are the most important criteria to look at when selecting a stirrer. They recommend the use of an anchor-type stirrer with a baffled tank.…”
Section: Polymerization Equipmentmentioning
confidence: 99%
“…Two well-known fluorinated surfactants are the ammonium salt of perfluorooctanoate (PFOA) and perfluorooctane sulfonate (C 8 F 17 SO 3 X, where X = K, Na, H). PFOA plays a key role in the emulsion or dispersion polymerization process to help incorporate hydrophobic monomers into the latex polymer, especially fluorinated monomers such as tetrafluoroethylene and other C 2 -C 3 alkenes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Polytetrafluoroethylene is the most important species in the fluorine-containing polymer and it is applied in many industrial areas, such as aerospace and medical areas. In China, PTFE is mainly obtained from suspension polymerization, but the PTFE from dispersion polymerization [1][2][3] which contains superior performance and is used to apply in the preparation of expanded porous products and hydraulic hose products is so less. There is a great gap in the performance of the dispersion resin compared with the foreign countries.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of industry, the size of the PTFE's demand has become a national economic indicator, so dealing with the control system of the production process of PTFE not only can improve the quality of the product and reduce energy consumption during the reaction, but also can provide guidance and advise to the scene of the process operation. The PTFE emulsion obtained from TFE dispersion polymerization has been applied in many important areas; foreign researchers have done a lot of work in the synthesis of fluorinated polymer emulsion and made good results in the application of research [4][5][6][7][8]. Some patents about it are implied in the industrial area successfully.…”
Section: Introductionmentioning
confidence: 99%